1987
DOI: 10.1523/jneurosci.07-03-00621.1987
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cholinergic neurons and the expression of morphine withdrawal symptoms in the rat

Abstract: Behavioral and autonomic signs of the morphine withdrawal syndrome were measured in dependent rats injected with the opiate antagonist naloxone. The purpose of this study was to determine whether spinal cholinergic pathways play a role in the expression of spinally mediated withdrawal symptoms. lntrathecal (i.t.) administration of 1 pg carbachol or 5 ccg neostigmine resulted in increases in mean anterial pressure (MAP) of 32 and 45 mm Hg, respectively, in conscious, freely moving rats. The pressor response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It was found in the present study that atropine pretreatment dose-dependently reduced the incidence of occurrence of faecal passage and muscle twitching following naloxone injection. This is in agreement with the findings of Chang et al (1984) and Marshall & Buccafusco (1987). However, the current investigation also revealed that atropine pretreatment did not markedly affect the circulatory depression or the occurrence of cardiac extrasystoles after naloxone administration.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It was found in the present study that atropine pretreatment dose-dependently reduced the incidence of occurrence of faecal passage and muscle twitching following naloxone injection. This is in agreement with the findings of Chang et al (1984) and Marshall & Buccafusco (1987). However, the current investigation also revealed that atropine pretreatment did not markedly affect the circulatory depression or the occurrence of cardiac extrasystoles after naloxone administration.…”
Section: Discussionsupporting
confidence: 94%
“…This indicates that cholinergic hyperactivity is not involved in the cardiovascular responses of chronically morphine-treated rats to naloxone-precipitated opiate withdrawal. It may not be reasonable to compare this postulation with that of Marshall & Buccafusco (1987) who made their observations in conscious and freely moving morphine-dependent rats. Based on the preventive effects of intrathecal injection of atropine or hemicholinium-3, they suggested that the blood pressure increases induced by naloxone administration resulted from central cholinergic hyperactivity which evoked an augmentation of sympathetic activity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the mechanism is unclear, cholinergic stimulation at the level of the spinal cord typically augments sympathetic activity and results in hypertension. Anticholinergic administration to rats experiencing opioid withdrawal results in a blunting of autonomic pressor response; however, this requires an intact spinal cord, suggesting a descending spinal cholinergic pathway that facilitates the autonomic response to IT opioid withdrawal 66,67 . This cholinergic excitatory descending pathway activates sympathoexcitatory preganglionic synapses in the case of an intact spinal cord, and IT clonidine reduces post‐withdrawal increases in MAP via interaction with cholinergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Around this same time Dr. Buccafusco also began working in the field of drug abuse research, the beginnings of his long time participation in the Veteran's Administration Merit system. These studies focused on the role of central cholinergic neurons in the development of physical dependence on opiates, the expression of withdrawal symptoms, and the return to drug-seeking behavior [4]. …”
Section: Introductionmentioning
confidence: 99%